2012
DOI: 10.1007/s10337-012-2339-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the HPLC Method for Simultaneous Determination of Lidocaine Hydrochloride and Tribenoside Along with Their Impurities Supported by the QSRR Approach

Abstract: A new liquid chromatographic (LC) method for simultaneous determination of lidocaine hydrochloride (LH) and tribenoside (TR) along with their related compounds in pharmaceutical preparations is described. Satisfactory LC separation of all analytes after the liquid–liquid extraction (LLE) procedure with ethanol was performed on a C18 column using a gradient elution of a mixture of acetonitrile and 0.1 % orthophosphoric acid as the mobile phase. The procedure was validated according to the ICH guidelines. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Several stability-indicating HPLC methods for the independent analysis of acyclovir (Bahrami, Mirzaeei, & Kiani, 2005;Brown, White, Chu, & Bartlett, 2002;Dao, Jiao, & Zhong, 2008;Fernández, Sepúlveda, Aránguiz, & von Plessing, 2003;Hasan, Chander, Ali, Baboota, & Ali, 2011;Huidobro, Ruperez, & Barbas, 2005;Stagni, Ali, & Weng, 2004;Tzanavaras & Themelis, 2007) or lidocaine (Gebauer, McClure, & Vlahakis, 2001;Malenovic, Medenica, Ivanovic, Jancic, & Markovic, 2005;Pendela, Kahsay, Baekelandt, Van Schepdael, & Adams, 2011;Plenis, Konieczna, Miękus, & Bączek, 2013;Prathyusha, Shanmugasundaram, & Naidu, 2013) in various formulations have been reported in the literature. To the best of our knowledge, no HPLC method has been reported for the simultaneous determination of acyclovir and lidocaine in combination formulations so far.…”
Section: Introductionmentioning
confidence: 99%
“…Several stability-indicating HPLC methods for the independent analysis of acyclovir (Bahrami, Mirzaeei, & Kiani, 2005;Brown, White, Chu, & Bartlett, 2002;Dao, Jiao, & Zhong, 2008;Fernández, Sepúlveda, Aránguiz, & von Plessing, 2003;Hasan, Chander, Ali, Baboota, & Ali, 2011;Huidobro, Ruperez, & Barbas, 2005;Stagni, Ali, & Weng, 2004;Tzanavaras & Themelis, 2007) or lidocaine (Gebauer, McClure, & Vlahakis, 2001;Malenovic, Medenica, Ivanovic, Jancic, & Markovic, 2005;Pendela, Kahsay, Baekelandt, Van Schepdael, & Adams, 2011;Plenis, Konieczna, Miękus, & Bączek, 2013;Prathyusha, Shanmugasundaram, & Naidu, 2013) in various formulations have been reported in the literature. To the best of our knowledge, no HPLC method has been reported for the simultaneous determination of acyclovir and lidocaine in combination formulations so far.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine Prilocaine and Lidocaine, many studies have been reported in literature. Several spectrophotometric [4][5][6], chromatographic [7][8][9][10][11][12][13][14][15][16][17][18], LC-MS/MS [19][20][21] and GC-MS [22][23][24] and capillary electrophoresis [25] techniques were developed in order to determine Prilocaine and Lidocaine in both pharmaceutical preparations and human plasma. The aim of the present work is to develop and validate a new high performance liquid chromatography (HPLC) and high performance thin layer chromatography (HPTLC) methods for determination of Prilocaine and Lidocaine in topical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…To determine PLC and LDC, many studies have been reported in literature. Several spectrophotometric [4][5][6], chromatographic [7][8][9][10][11][12][13][14][15][16][17][18], liquid chromatography-tandem mass spectrometry [19][20][21], and gas chromatography-mass spectrometry [22][23][24] and capillary electrophoresis [25] techniques were developed to determine PLC and LDC in both pharmaceutical preparations and human plasma. The aim of the present work is to develop and validate a new high-performance liquid chromatography (HPLC) method for determination of PLC and LDC in topical formulation.…”
Section: Introductionmentioning
confidence: 99%